Pelatihan Pembuatan Gundukan Untuk Meningkatkan Kemampuan Hidup Tanaman Shorea Balangeran (Korth) Burck Di Lahan Gambut Desa Tanjung Sangalang Dan Penda Barania Kabupaten Pulang Pisau Kalimantan Tengah - Rosana Elvince (Universitas Tanjungpura, 2022)
This activity was carried out on October 21, 2021 in Tanjung Sangalang and Penda Barania Villages, to provide information to the community in the balangeran revegetation activity and also to conduct a plot demonstration to provide examples of how to increase the growth of Shorea balangeran. As villages that is included in a peat area which is needed to be restorated by the Ministry of the Environment, therefore, the activity that can be developed in both villages was the revegetation of the balangeran plant. The revegetation of the balangeran plant was chosen as one of the Community Work Plans (RKM) in order to restore damaged peatlands in both areas. The unsuccessful revegetation of the balangeran plant carried out by the people in the two villages was caused by the lack of insight and knowledge of the community regarding the proper revegetation system to support the growth of the balangeran plant. Making mounds is one way that can be applied in order to maintain the viability of the balangeran plants in flooded environmental conditions. Balangeran plants that live in flooded areas with a mound system still show good growth. The villages of Tanjung Sangalang and Penda Barania are villages that are often inundated due to floods. To increase the success of revegetation of the balangeran plant, which is a local peat swamp plant and has a high economic value, the planting of balangeran with a mound system is the right system to be applied to the two villages. The training on making mounds in the two villages went smoothly which was attended by the community from representatives of each village.